2013
DOI: 10.3109/08880018.2013.771240
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Whole-Body Cooling on Hematological and Coagulation Parameters in Asphyxic Newborns

Abstract: Although moderate therapeutic hypothermia is the only proven neuroprotective therapy in neonatal hypoxic ischemic encephalopathy secondary to perinatal asphyxia (PA), there is lack of data for its effect on hemostasis. To investigate the effect of neonatal asphyxia on hemostasis and to evaluate the effect of whole body cooling on hematological parameters. Hematological parameters evaluated on the first day of patients with PA before start of hypothermia were compared with those of healthy controls. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…Our data suggest that therapeutic hypothermia does not independently cause neonatal thrombocytopenia. Hypothermia for 72 hours has recently become a common and effective means of improving neurodevelopment of term neonates after perinatal asphyxia . Hypothermia does adversely affect PLT function, as manifested by prolongation of the bleeding time and lengthening of the PFA100 closure time .…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that therapeutic hypothermia does not independently cause neonatal thrombocytopenia. Hypothermia for 72 hours has recently become a common and effective means of improving neurodevelopment of term neonates after perinatal asphyxia . Hypothermia does adversely affect PLT function, as manifested by prolongation of the bleeding time and lengthening of the PFA100 closure time .…”
Section: Discussionmentioning
confidence: 99%
“…In one study, as many as one third of infants arrived in NICU with a core temperature of <33°C [23]. Deep hypothermia may induce bradycardia and arrhythmia [20], thrombocytopaenia [6] requiring platelet transfusion [21] although overall haemostasis may not be affected [22]. …”
Section: Discussionmentioning
confidence: 99%
“…13 A recently published study showed that neonatal platelet function is impaired by therapeutic hypothermia, a phenomenon that is reversible by reestablishing regular body temperature. 14 Moreover, plasmatic coagulation factors in neonates are also out of normal ranges during therapeutic hypothermia, 15 and in contrast to the results of the RCTs, some authors described significantly higher prothrombin times and lower platelet counts with more patients requiring plasma and platelet transfusions in the hypothermic group. 16 To add some diagnostic considerations, measurement of platelet function is not available in the routine laboratory workup at the NICU.…”
Section: Discussionmentioning
confidence: 99%